Communicating with the public conversation analytic studies - Waring, Hansun Zhang; Reddington, Elizabeth (Bloomsbury Academic, 2022)
"This book offers a collection of conversation analytic investigations, focusing on the efforts of one US-based philanthropic organization to communicate its mission of improving public health through its funding of health-related research and programming. In contrast to big speeches and news interviews, much communication with the public involves routine communications undertaken by institutional representatives : this book considers through conversation analysis how this can be done most effectively"--Provided by publisher.